Maximizing Magnesiation Capacity of Nanowire Cluster Oxides by Conductive Macromolecule Pillaring and Multication Intercalation. Issue 30 (3rd July 2021) - Yao, Zhenguo; Yu, Yifan; Wu, Qingping; Cui, Mengnan; Zhou, Xuejun; Liu, Jianjun; Li, Chilin
Abstract: Magnesium metal batteries (MMBs) have obtained the reputation owing to the high volumetric capacity, low reduction potential, and dendrite‐free deposition behavior of the Mg metal anode. However, the bivalent nature of the Mg 2+ causes its strong coulombic interaction with the cathode host, which limits the reaction kinetics and reversibility of MMBs, especially based on oxide cathodes. Herein, a synergetic modulation of host pillaring and electrolyte formulation is proposed to activate the layered V2 O5 cathode with expanded interlayers via sequential intercalations of poly(3, 4‐ethylenedioxythiophene) (PEDOT) and cetyltrimethylammonium bromide (CTAB). The preservation of bundled nanowire texture, copillaring behavior of PEDOT and CTA +, dual‐insertion mode of Mg 2+ and MgCl + at cathode side enable the better charge transfers in both the bulk and interface paths as well as the interaction mitigation effect between Mg‐species cations and host lattices. The introduction of CTA + as electrolyte additive can also lower the interface resistance and smoothen the Mg anode morphology. These modifications endow the full cells coupled with metallic Mg anode with the maximized reversible capacity (288.7 mAh g ‐1 ) and superior cyclability (over 500 cycles at 500 mA g ‐1 ), superior to most already reported Mg‐ion shuttle batteries even based on passivation‐resistant non‐Mg anodes or operated at higher temperatures. Abstract : A synergetic modulation of host pillaring and electrolyte formulation is proposed to activate the layered V2 O5 cathode with expanded interlayers via sequential intercalations of poly(3, 4‐ethylenedioxythiophene) and cetyltrimethylammonium bromide (CTAB). The introduction of CTA + additive lowers the interface resistance and smoothens the Mg anode morphology. These modifications endow the Mg metal batteries with maximized reversible capacity and superior cyclability.